Corpora e formação de tradutores para o contexto profissional de uma universidade pública federal no Estado do Pará: propostas de unidades didáticas - Souza, Beatriz Pereira de (2022)
This research demonstrated the possibility of manipulating corpus tools to obtain data that support materials for the translator training. For this purpose, we used as linguistic corpus the abstracts of academic monographs from the “Universidade Federal Rural da Amazônia – Campus Parauapebas” in all areas of knowledge from courses in the Campus, Administration, Agronomy, Forestry Engineering, Production Engineering and Animal Science. The frequency of words and terms found were compiled, and the pattern in the translation choices of specific terms to the areas of the courses and how this research process can help and facilitate the translator's work were verified. We use translation studies as a theoretical basis, making an overview of the studies by Bassnett (2002), Pym (2017), especially, and also taking into account the works of Plaza (2003), Levý (2011), Larson (1997) , Berman (2007), Newmark (1988), Campos (1986) and Guerini et al. (2013); later, we based the research on corpora studies, by Laviosa (2002), Tagnin (2015), Magalhães (2013), Sardinha (2004); and finally, on the training of translators, use as a source Pagano et al. (2000), Colfer (2012) Pereira et al. (2018) and Nord (2007, 2016), in addition to studies on Translation Competence by the PACTE group. We demonstrate in practice the use of the Lancsbox tool, showing the results found and the possibilities of handling this information obtained for the training of translators. Were propose three didactic units, Pais (2013), which are stages of the teaching and learning process, in this case, the stages were designed for the teaching and learning of translation practices that can be implemented in the context from which the data was sought to make the units, in researched university, for the training of translators who work there. It was the purpose of this work to contribute as a source of innovation in research in the field of translation, training of translators, corpora and specialty studies, demonstrating how interdisciplinary translation studies are and can even have a pedagogical character.